權利與善——論同性婚姻: Rights and Goods: On Same-sex Marriage - FANG, Xudong (International Journal of Chinese & Comparative Philosophy of Medicine, 2018)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文由兩個部分構成，第一部分闡述了不反對同性婚姻合法化的理由，逐一討論了對同性婚姻合法化的五種反對意見，認為它們都不成立。第二部分論述了儒家推崇異性婚姻的原因，其主要考慮是同性婚姻不能像異性婚姻那樣可以提供倫理的完整性。作者強調，作為公民權利，同性婚姻可以被自由追求，但作為儒家則以異性婚姻為婚姻的理想模式。前者事關權利，後者事關“善”，有各自的界限，不得逾越。 This paper consists of two parts. In the first part, the author refutes, one by one, five objections to the legalization of same-sex marriage, including arguments grounded in naturalness, origin, reductio ad absurdum, compromising traditional marriage, and Jiang Qing’s doctrine of particular human rights. The strongest reason for advocating the legalization of same-sex marriage is the doctrine of equal rights. As contemporary people, we have no reason to deny that all individuals have equal rights. The second part discusses why Confucianism prefers heterosexual marriage. The main consideration is that same-sex marriages cannot provide ethical integrity, as heterosexual marriages do. The author emphasizes that, as a civil right, same-sex marriage can be pursued freely, but for a Confucian, heterosexual marriage is the ideal mode of marriage. The former concerns what is “right,” whereas the latter relates to what is “good.” There is an insurmountable boundary between right and good. DOWNLOAD HISTORY | This article has been downloaded 423 times in Digital Commons before migrating into this platform.